KAJIAN PERUBAHAN MANUAL SUPERVISI JALAN DENGAN SPESIFIKASI UMUM 2018 BINA MARGA - Bertho Orbain Sowolino; Prayoga Luthfil Hadi; Zakaria Mujahid; Wimpy Santosa (Jurnal Transportasi, 2019)
Abstract In order to support the acceleration of Indonesia's economic growth, massive infrastructure development must be carried out. The movement of goods and people must be able to run smoothly to accelerate economic growth. One type of infrastructure that can provide direct support is road infrastructure. Roads have an important role in regional development both from economic, social, cultural and environmental aspects. With its flexible nature, it can reach various regions and its development methods are relatively easy, the road being a favorite infrastructure to be developed. To achieve good quality road construction, a general specification must be met. In 2014, the Directorate General of Highways issued the 2010 General Specification (Revision 3) which was completed with the Road Supervision Manual document that referred to the specification. But with the increasing need for quality road construction and increasing awareness of the importance of maintenance activities, in 2018 the Directorate General of Highways issued a General Specification 2018. Therefore, it is necessary to understand the changes of the General Specifications and changes in the Road Supervision Manual. Keywords: infrastructure development, road construction, general spesification, supervision manual  Abstrak Untuk mendukung percepatan pertumbuhan ekonomi Indonesia, pembangunan infrastruktur secara masif harus dilakukan. Pergerakan barang dan orang harus dapat berjalan secara lancar untuk mempercepat pertumbuhan ekonomi. Sampai saat ini, salah satu jenis infrastruktur yang dapat memberikan dukungan secara langsung adalah infrastruktur jalan. Jalan memiliki peranan penting dalam pengembangan wilayah, dari aspek-aspek ekonomi, sosial, budaya, dan lingkungan. Dengan sifatnya yang fleksibel, karena dapat menjangkau berbagai daerah dan metode pembangunannya yang relatif mudah, jalan menjadi infrastruktur favorit untuk dikembangkan. Untuk menghasilkan kualitas pembangunan jalan yang baik diperlukan suatu spesifikasi umum yang harus dipenuhi. Pada tahun 2014, Direktorat Jenderal Bina Marga mengeluarkan Spesifikasi Umum 2010 Revisi 3 yang dilengkapi dengan dokumen Manual Supervisi Jalan yang mengacu pada spesifikasi tersebut. Namun, dengan meningkatnya kebutuhan akan kualitas pembangunan jalan serta meningkatnya kesadaran akan pen-tingnya kegiatan pemeliharaan, pada tahun 2018 Direktorat Jenderal Bina Marga mengeluarkan Spesifikasi Umum 2018. Untuk itu, diperlukan pemahaman terhadap perubahan Spesifikasi Umum tersebut dan perubahan Manual Supervisi Jalan. Kata-kata kunci: pembangunan infrastruktur, pembangunan jalan, spesifikasi umum, manual supervisi